Analisis Kesiapan Puskesmas dalam Melaksanakan Kebijakan Integrasi Pelayanan Kesehatan Primer - Chreisye K. F. Mandagi; Erica Umboh; Christiani Wauran; Chrismas Malensang; Leony Palit; Jessica Vinza; Ribianti Darize; Godlife Apita (Universitas Pahlawan Tuanku Tambusai, 2026)
The transformation of primary healthcare services represents a government initiative to enhance the quality of integrated, holistic, and community-oriented healthcare services. As the main healthcare facility, the Community Health Center (Puskesmas) plays a crucial role in supporting the implementation of the Primary Healthcare Integration (Integrasi Layanan Kesehatan Primer or ILP) policy. This study aims to analyze the extent of Puskesmas readiness inimplementing the ILP policy using a literature review method. Data sources were gathered from national scientific articles via Google Scholar spanning the years 2023–2025. The results indicated that six articles met the research criteria. The findings demonstrated that changes in primary healthcare servicesexert a positive effect on improving service quality through community health workers' (kader) competency enhancement,training, mentoring, and the utilization of digital technology. However, policy implementation continues to face several challenges, such as the limited capacity of kader in providing health education and performing anthropometric measurements, a lack of infrastructure and internet access, sub-optimal Electronic Medical Record (Rekam Medis Elektronik) systems, and inefficient service coordination. Nonetheless, continuous training, human resource capacity building, digital infrastructure improvements, and regular evaluations have proven effective in enhancing the efficiency ofprimary healthcare services. Consequently, the implementation of Primary Healthcare Integration can proceed optimally and sustainably to elevate public health status in Indonesia. This study is expected to serve as a reference for the government and healthcare providers in reinforcing the readiness of Puskesmas to navigate the comprehensive and continuous changes in primary healthcare services in the future.